6x+9=4x+13

Simple and best practice solution for 6x+9=4x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+9=4x+13 equation:


Simplifying
6x + 9 = 4x + 13

Reorder the terms:
9 + 6x = 4x + 13

Reorder the terms:
9 + 6x = 13 + 4x

Solving
9 + 6x = 13 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
9 + 6x + -4x = 13 + 4x + -4x

Combine like terms: 6x + -4x = 2x
9 + 2x = 13 + 4x + -4x

Combine like terms: 4x + -4x = 0
9 + 2x = 13 + 0
9 + 2x = 13

Add '-9' to each side of the equation.
9 + -9 + 2x = 13 + -9

Combine like terms: 9 + -9 = 0
0 + 2x = 13 + -9
2x = 13 + -9

Combine like terms: 13 + -9 = 4
2x = 4

Divide each side by '2'.
x = 2

Simplifying
x = 2

See similar equations:

| 4x-(2x-3)=14 | | 0.6(x+100)+0.4x=85 | | 4s+2s-6=6 | | 7x+18=-2(x-18) | | -11/20=x-13/16 | | -11=14+x | | 4x+3=22x | | 2x-13=8-6x+3 | | 2(4x+3)=5(3x+4) | | x(5x+21)+18=0 | | 5p-100=x | | 84-7x=11x+20 | | 2(5x+8)=3(4x-2) | | 2x+19=9x-44 | | 9+2.7t=4.8t-9 | | 8x-3y=-24 | | x-4+99=8 | | 4-7x=3x+1 | | 3x+47=7x+10 | | 12x-24-8x=-6x+16 | | 5x+13-4x=7+4x-6 | | 3x+14=85-8x | | 1/4=z+7/4 | | 14x+120+10x=360 | | 3[6x-4]=-52 | | 4+7(-12+x)=-38 | | 24+14x=x | | 3y+z=am | | [6x-4]=-52 | | 4x-10=6x+12 | | 14x+24=x | | 6x-4=-52 |

Equations solver categories